2018
DOI: 10.4172/2155-6148.1000849
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Delivery and Labour Analgesia: A Study of Preference in Portuguese Pregnant Women

Abstract: Background: Portugal has had one of the highest cesarean rates in Europe, possibly influenced by patient preferences. A reduction in the prevalence of these rates due to safety, quality, and concern with costs is one of the current goals of obstetric care. Fear of pain, often associated with vaginal delivery, is one of the reasons why pregnant women might prefer a cesarean section. Objective: The aim of this study was to identify the type of delivery and anaesthesia/analgesia preferred, as well as the reasons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Other studies have reported an increase in the global CDR average from 12.4% to 18.6% and a rate of increase of 4.2% per annum. 9 , 10 Assisted reproductive technology, maternal age, maternal health condition, obstetrical complications, smoking during pregnancy, and socioeconomic status have been reported as factors contributing to increasing CDRs globally. 11 Similar experiences have been reported in sub-Saharan Africa (SSA), where only 7.3% of newborns are born via CD.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported an increase in the global CDR average from 12.4% to 18.6% and a rate of increase of 4.2% per annum. 9 , 10 Assisted reproductive technology, maternal age, maternal health condition, obstetrical complications, smoking during pregnancy, and socioeconomic status have been reported as factors contributing to increasing CDRs globally. 11 Similar experiences have been reported in sub-Saharan Africa (SSA), where only 7.3% of newborns are born via CD.…”
Section: Introductionmentioning
confidence: 99%